The Islamic Funerary Inscriptions of Bahrain Pre-1317 AH/1900 AD - Insoll, Timothy, (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2019)
In The Islamic Funerary Inscriptions of Bahrain, Pre-1317 AH/1900 AD , the authors present a study of the funerary inscriptions based upon fieldwork completed in Bahrain between 2013-2015. A comprehensive illustrated catalogue of 150 gravestones in 26 locations is provided with transcription of the inscriptions into modern Arabic and translation into English. Subjects considered include: the history of Islamic burial, gravestone, and cemetery research on Bahrain, gravestone chronology, gravestone and cemetery types, stone sources and gravestone manufacture, the gravestone inscriptions, content, iconography and decoration, and the archaeology of the shrines and cemeteries in which some of the gravestones were found, contemporary practices relating to cemeteries, graves, and gravestones, the threats facing the gravestones, and management options for protecting and presenting the gravestones.